Quintuple Helix Lens for Transformation: An Okayama Model of Education for Sustainable Development - Zen, Irina Safitri; Shibakawa, Hiroko (Frontiers in Sustainability, 2022)
What makes society transform? Using the Quintuple Helix Model of social innovation, this study examines how the Okayama ESD project has transformed the local community and its people, and how this has led to a global recognition. The city is known as a world leader in ESD and their unique approach is called Okayama Model of ESD. This study further looks at the institutional configuration, what the elements contributed to knowledge co-creation and how the key actors interacted to contribute to societal transformation through knowledge, social innovation and institutional setting. The goal of this study is to outline the Okayama Model of ESD by using the QHM lens constituted of five helices; education, political, society, economy and the natural environment. This study applies a qualitative research method, in which key actors who contribute most to the development of the ESD Okayama model are identified by content analysis and semi-structured interviews which are conducted using the life history method. The result shows that the firm ground of the political sub-system facilitates the interaction among the stakeholders in the three sub-system; education, social and natural-environment, which ultimately contributes to the joining of the economic subsystem and the initiation of the knowledge circulation process. Transformation necessitates a city-wide approach involving a network of multiple actors to collaborate for knowledge co-creation and circulation as well as the establishment of a new social values system. The study revealed several key points of local action that accelerated the transformation process by helping in the value creation, knowledge convergence and system interaction which was instilled early through all forms of education, multiple actors interaction that shape through the ESD Project that stimulates the triangulation of mind, hearts and hand. In this way, the city of Okayama functions as a living laboratory for the Okayama model of ESD. This situation naturally promotes Mode 3 of the knowledge co-creation system, and the principles of civic collaboration and citizen engagement developed through the Okayama ESD model have been elaborated in the prefecture-wide vision statement.